2021
DOI: 10.3390/molecules26196086
|View full text |Cite
|
Sign up to set email alerts
|

Cudraxanthone D Ameliorates Psoriasis-like Skin Inflammation in an Imiquimod-Induced Mouse Model via Inhibiting the Inflammatory Signaling Pathways

Abstract: Psoriasis is a chronic inflammatory skin disease accompanied by excessive keratinocyte proliferation. Corticosteroids, vitamin D3 analogs, and calcineurin inhibitors, which are used to treat psoriasis, have diverse adverse effects, whereas natural products are popular due to their high efficiency and relatively low toxicity. The roots of the Cudrania tricuspidata (C. tricuspidata) are known to have diverse pharmacological effects, among which the anti-inflammatory effect is reported as a potential therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Enhanced expression of IL-1β mRNA has been observed in vivo , in IMQ-induced mice ( Shou et al, 2021 ) ( Deng et al, 2019 ) ( Tang et al, 2021 ). This tendency was in accordance with the result of one previous cell experiment ( Kim et al, 2021 ). Aberrant or excessive activation of the classical caspase-1 path is associated with many autoinflammatory, autoimmune, and metabolic diseases ( Shi et al, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…Enhanced expression of IL-1β mRNA has been observed in vivo , in IMQ-induced mice ( Shou et al, 2021 ) ( Deng et al, 2019 ) ( Tang et al, 2021 ). This tendency was in accordance with the result of one previous cell experiment ( Kim et al, 2021 ). Aberrant or excessive activation of the classical caspase-1 path is associated with many autoinflammatory, autoimmune, and metabolic diseases ( Shi et al, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…suggested that some of these IFN-induced transcripts (STAT1, IFIT1, and IFIT3) were key genes involved in psoriasis development ( 60 ). Higher levels of STAT1 were confirmed in psoriatic skin and STAT1 phosphorylation was increased following IFN-α or IFN-γ stimulation ( 61 65 ). In addition, Huang’s study revealed elevated levels of OAS1, OAS2, and OAS3 in psoriatic skin and serum and these IFN-induced enzymes decreased after biological therapies ( 66 ).…”
Section: Biomarkers Of Platelet Activation Associated With Psoriasis ...mentioning
confidence: 96%
“…Moreover, CD suppressed TNF-α, immunoglobulin G2a, and myeloperoxidase serum levels and inhibited Th1/Th17-cell expression in splenocytes. In TNF-α/IFN-γ-activated keratinocytes, CD suppressed inflammatory cytokine expression by modulating STAT1 phosphorylation and NF-kB nuclear translocation [ 113 ]. These findings highlight the potential of CD as a therapeutic candidate for managing psoriasis.…”
Section: Natural Product-derived Compounds For Psoriasis Therapeuticsmentioning
confidence: 99%